Chitosan-based nanoparticle co-delivery of docetaxel and curcumin ameliorates anti-tumor chemoimmunotherapy in lung cancer. (15th September 2021) - Zhu, Xiongjie; Yu, Zhongjian; Feng, Longbao; Deng, Lian; Fang, Zhaobi; Liu, Zhile; Li, Ying; Wu, Xiaoran; Qin, Lingyu; Guo, Rui; Zheng, Yanfang
Abstract: The application of traditional chemotherapy drugs for lung cancer has obvious limitations, such as toxic side effects, uncontrolled drug-release, poor bioavailability, and drug-resistance. Thus, to address the limitations of free drugs and improve treatment effects, we developed novel T7 peptide-modified nanoparticles (T7-CMCS-BAPE, CBT) based on carboxymethyl chitosan (CMCS), which is capable of targeted binding to the transferrin receptor (TfR) expressed on lung cancer cells and precisely regulating drug-release according to the pH value and reactive oxygen species (ROS) level. The results showed that the drug-loading content of docetaxel (DTX) and curcumin (CUR) was approximately 7.82% and 6.48%, respectively. Good biosafety was obtained even when the concentration was as high as 500 μg/mL. More importantly, the T7-CMCS-BAPE-DTX/CUR (CBT-DC) complexes exhibited better in vitro and in vivo anti-tumor effects than DTX monotherapy and other nanocarriers loaded with DTX and CUR alone. Furthermore, we determined that CBT-DC can ameliorate the immunosuppressive micro-environment to promote the inhibition of tumor growth. Collectively, the current findings help lay the foundation for combinatorial lung cancer treatment. Highlights: ROS/pH-responsive nanoparticles mediated DTX and CUR co-delivery to lung cancer. The nanomedicine exhibited better antitumor effects compared with free drug. Amelioration of immunosuppressive microenvironment could be achieved by CBT-DC.